Technology Push vs. Market Pull in Technology University Innovation Commercialization Case Study: ITB - Ameka, Indriany (Information Management and Business Review, 2013)
Technology-based innovation can comes either from market needs (market pull) then obtained the discovery of new innovation technology to help meet the needs of the community or from new invention which was later adapted by the community (technology push) that become useful new needs. The purpose of this paper is to determine the implications that what works better between technology push or market pull in technological innovation carried out by researchers in creating new technologies. In this paper, the study used the example of one of the universities in Indonesia, the ITB because it has a research institute that more active than any other university in Indonesia. Sample taken from the new product invention that have been successfully commercialized or not. To know whether successfully commercialized inventions are more likely depart from the market pull or technology push. We got the result of this research from technology innovation product that has been patented, from dept interviews by the researchers in ITB, and from focus group discussion among the junior researchers. The result of technology innovation product that only has been patented and the technology innovation product that already is commercialized and used by many people will be different. We will see the beginning of the idea appearance and the commercialization of their product innovation in the market from the researchers.